51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-413
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Surfaces for Mitigation of Insect Residue Adhesion

Abstract: Maintenance of laminar flow under operational flight conditions is being investigated under NASA's Environmentally Responsible Aviation (ERA) Program. Among the challenges with natural laminar flow is the accretion of residues from insect impacts incurred during takeoff or landing. Depending on air speed, temperature, and wing structure, the critical residue height for laminar flow disruption can be as low as 4 µm near the leading edge. In this study, engineered surfaces designed to minimize insect residue adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Similarly, more recent work conducted by Kok et al [57] and Wohl et al [51,53], suggested that surfaces exhibiting hierarchical or multi-scale roughness structures, permit insect residue on low energy surfaces to adopt a Cassie-Baxter wetting state, as air is trapped in the cavities of the surface [130][131][132]. Surfaces possessing low surface energy hierarchical roughness designs have also been shown to be effective in bioadhesion control [133]; such surfaces are found in nature (e.g.…”
Section: Surface Roughnessmentioning
confidence: 62%
See 4 more Smart Citations
“…Similarly, more recent work conducted by Kok et al [57] and Wohl et al [51,53], suggested that surfaces exhibiting hierarchical or multi-scale roughness structures, permit insect residue on low energy surfaces to adopt a Cassie-Baxter wetting state, as air is trapped in the cavities of the surface [130][131][132]. Surfaces possessing low surface energy hierarchical roughness designs have also been shown to be effective in bioadhesion control [133]; such surfaces are found in nature (e.g.…”
Section: Surface Roughnessmentioning
confidence: 62%
“…Other tests conducted in an ice-crystal environment showed that even for short duration, this effect is sufficient to remove or reduce insect debris below the critical height [23]. Erosion of insects has also been reported by Henke [124] within the A320 HLFC fin tests and suggested by Wohl et al for disappearance of insect residue in digital photographs obtained during flight tests performed with experimental coatings [53]. The work conducted by Lachmann [83] indicated that insect deposits collected only during take-off also showed higher adhesion compared to those collected on takeoff that subsequently flew a complete flight cycle.…”
Section: Natural Cleaning In Flightmentioning
confidence: 81%
See 3 more Smart Citations